2020
DOI: 10.1109/access.2020.3041432
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the Android Permissions System

Abstract: Android is one of the most essential and highly used operating systems. Android permissions system is a core security component that offers an access-control mechanism to protect system resources and users' privacy. As such, it has experienced continuous change over each Android release. However, previous research on the permissions system has employed static analysis techniques. Furthermore, most of these studies are outdated, covering older versions of Android. This paper aims to discuss the permissions syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 39 publications
0
19
0
4
Order By: Relevance
“…With the growth of Android in the market, malicious applications have also surfaced, which has driven many studies and research works towards it. Iman and Aala [25] proposed a comprehensive analysis of Android permission systems. They provided important insight into the permission system evolution over the years and how permission usage has increased up to 73.33% in top applications by 2020.…”
Section: Related Workmentioning
confidence: 99%
“…With the growth of Android in the market, malicious applications have also surfaced, which has driven many studies and research works towards it. Iman and Aala [25] proposed a comprehensive analysis of Android permission systems. They provided important insight into the permission system evolution over the years and how permission usage has increased up to 73.33% in top applications by 2020.…”
Section: Related Workmentioning
confidence: 99%
“…Ek olarak, vaka çalışmasının sonuçları hem satıcılar hem de geliştiriciler tarafından izin dağıtımının anlaşılmasına katkıda bulunur. Son olarak, izne dayalı güvenlik geliştirmeleriyle ilgili bir sonuç olarak Android izin sisteminin çeşitli güvenlik sorunları ile karşı karşıya olduğunu ortaya koymaktadır [5].…”
Section: Literatür İncelemesiunclassified
“…This section of the paper provides a brief examination of some of the related works carried out. Almomani and Al Khayer [1] discussed the Android permission systems by providing a general overview of the Android control mechanism. The study identified and grouped Android dangerous permissions based on their API levels.…”
Section: Permission-based Detection and Feature Extractionmentioning
confidence: 99%
“…Among the smartphone platforms, Android is the most popular. A previous study [1] showed that Android owns 74.5% of the mobile device marketplace. The popularity of Android has caused an increase in third-party application development to respond to the shift.…”
Section: Introductionmentioning
confidence: 99%